Analisis Desain Formulir Asesmen Awal Rawat Jalan Terkait SNARS Edisi 1.1 Elemen Penilaian AP 1.2 di RSBSA Bandung - Hendro Hendro; Sali Setiatin (Jurnal Health Sains, 2021)
The initial assessment was identified for new patients who came for outpatient treatment as basic information to determine the patient's condition and for follow-up care. Based on the results of observations at RSBSA Bandung that the initial outpatient assessment form is still less effective and efficient. So the hospital needs to review the initial outpatient assessment form, so that it can fulfill SNARS Edition 1.1 Assessment Elements of AP 1.2. The purpose of this study was to design an outpatient initial assessment form at RSBSA Bandung form based on SNARS Edition 1.1 Assessment Elements of AP 1.2. This study uses a qualitative case study approach. The subjects of this study included dentists, nurses and heads of medical records. The object of this research is the outpatient initial assessment form. Research data collection techniques by interview and observation. From the physical aspect, the form design uses white with A4 size cardboard, paper weight is 190grams and is rectangular in shape. From the anatomical aspect, there is no edition number and page number heading, no introduction and instructions, no body and no close notes. From the aspect of content, identity data already exists, patient medical data is not suitable for SNARS Edition 1.1 Elements of AP 1.2. Based on the results of research, it is necessary to design an outpatient initial assessment form based on SNARS Edition 1.1 related to AP 1.2 Assessment Elements.